Distortions, endogenous managerial skills and productivity differences - Dhritiman Bhattacharya; Nezih Guner; Gustavo Ventura (Institute for the Study of Labor (IZA), 2011)
We develop a span-of-control model where managerial skills are endogenous and the outcome of investments over the life cycle of managers. We calibrate this model to U.S plant-size data to quantify the effects of distortions that are correlated with the size of production units. These distortions lead to sharp reductions in plant productivity and the fraction of employment in large plants, with a quantitatively important role for managerial investments. We find that the model can account quite well for properties of Japanese size-distribution data, with a model-implied TFP of about 83% of the U.S. Distortions are critical in accounting for the differences in size distribution between the U.S. and Japan.
urn:nbn:de:101:1-201110053372
Keywords: O40; E23; 330; distortions; size; skill investments; productivity differences; Führungskräfte; Bildungsinvestition; Ökonomischer Anreiz; Betriebsgröße; Produktivität; Vergleich; USA; Japan